Prevalence of the integration status for human papillomavirus 16 in esophageal carcinoma samples - Li, Shuying; Shen, Haie; Li, Ji; Hou, Xiaoli; Zhang, Ke; Li, Jintao (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: To investigate the etiology of esophageal cancer (EC) related with human papillomavirus (HPV) infection. Materials and Methods: Fresh surgically resected tissue samples and clinical information were obtained from 189 patients. Genomic DNA was extracted, and HPV was detected using polymerase chain reaction (PCR) with HPV L1 gene primers of MY09/11; HPV16 was detected using HPV16 E6 type-specific primer sets. Copies of HPV16 E2, E6, and the human housekeeping gene β-actin were tested using quantitative PCR to analyze the relationship between HPV16 integration and esophageal squamous cell carcinoma and the relationship between the HPV16 integration status and clinical information of patients. Results: Of the 189 samples, 168 HPV-positive samples were detected, of which 76 were HPV16 positive. Among the HPV16 positive samples, 2 cases (E2/E6 ratio>1) were 2.6% (2/76) purely episomal, 65 (E2/E6 ratio between 0 and 1) were 85.6% (65/76) mixture of integrated and episomal, and 9 (E2/E6 ratio=0) were 11.8% (9/76) purely integrated. The results indicate that integration of HPV16 was more common in the host genome than in the episome genome. The prevalence rate of HPV16 integration is increasing with the pathological stage progression of esophageal carcinoma (EC). Conclusion: A high prevalence of HPV16 suggested that HPV16 has an etiological effect on the progress of EC. Integration of HPV16 is more common than episome genome in the host cells, indicating that continuous HPV infection is the key to esophageal epithelial cell malignant conversion and canceration. Cite this article as: Li S, Shen H, Li J, Hou X, Zhang K, Li J. Prevalence of Human papillomavirus 16 integration status in esophageal carcinoma samples. Turk J Gastroenterol 2018; 29: 157-63.